2016
DOI: 10.1177/0954405415606386
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of increasing ceramic shell permeability and optimizing casting shrinkage and tensile strength of the investment cast parts

Abstract: This study explores about enhancing the permeability of the ceramic shells used in the investment casting process using cheaply available sawdust particles. An increase in shell's permeability augments the cooling rate of the casting which enhances its mechanical properties. It was found that the inclusion of sawdust particles into the ceramic slurries exhibited positive impact on the shell's permeability. It is a well-known fact that electromagnetic stirring process increases the mechanical properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…e plates were sheared to nominal dimensions of 50 mm × 180 mm so that the grains aligned in the direction of the joint line. e experiments were performed on the plates in the rolling direction [11][12][13]. Figure 3 shows the geometric layout representation of HC steel for FSW.…”
Section: Materials Selectionmentioning
confidence: 99%
“…e plates were sheared to nominal dimensions of 50 mm × 180 mm so that the grains aligned in the direction of the joint line. e experiments were performed on the plates in the rolling direction [11][12][13]. Figure 3 shows the geometric layout representation of HC steel for FSW.…”
Section: Materials Selectionmentioning
confidence: 99%
“…Investment casting is an important industry expertise and has been widely used in various manufacturing fields due to its advantages of high precision, high shape complexity, and good adaptability to various alloys. [1][2][3] Singh and Singh 4 reviewed the development of this technique and demonstrated that the main steps of investment casting include wax mold pressing and assembly, mold preparation, dewaxing and mold baking, liquid metal pouring, mold cleaning and posttreatment of castings.…”
Section: Introductionmentioning
confidence: 99%